The Role Of Competence And Career Development In Improving Teacher Performance - Khoerunnisa, Asyifa; Rizqullah, Muhammad Naufal; Sulistyowati, Lisa Harry (LPPM of NAROTAMA UNIVERSITY, 2025)
This study aims to investigate the relationship between the professional development and competency of primary school teachers in West Java and their performance. A total sample of 176 teachers was selected using a quantitative research design. In order to verify validity, reliability, and traditional assumptions, data were gathered using questionnaires, observations, and interviews. SPSS software was used for analysis. Competence (X1) and career growth (X2) have a major impact on teacher performance (Y).